Peningkatan Proses Belajar Siswa Dengan Model Pembelajaran Make A Match Terhadap Hasil Belajar Pembelajaran Tematik Tema Tematik Tema 2 Subtema Pentingnya Makanan Sehat Bagi Tubuh Kelas V SD Negeri 102010 Liberia - Bina Limbong; Regina Fredika Sipayung (Al Yazidiy Jurnal Sosial Humaniora dan Pendidikan, 2024)
The aim of this research is to increase the level of activity and learning outcomes of students through implementing the make a match learning model. The research method applied is Classroom Action Research (PTK), with the research subject focusing on class V students. Data collection is carried out through tests, observations, and activeness assessment rubrics. Data analysis was carried out descriptively in both quantitative and qualitative aspects. The research results showed a significant increase in student learning activity. In the pre-cycle stage, there were 24 students (64.87%) who were identified as inactive. However, in cycle I, this figure decreased to 9 students (24.32%) who had reached a sufficient level of activeness. In cycle II, student activity increased significantly, reaching 31 students (83.78%) who were classified as active. Meanwhile, for learning outcomes, in the pre-cycle there were 15 students (41%) who achieved completeness. In cycle I, the number of students who completed increased to 20 students (54%), and in cycle II it reached 30 students (81%). Therefore, it can be concluded that through the application of the make a match learning model, there has been a real increase in the activity and learning outcomes of students in this class.